التحليل الحراري ثنائي البعد لخرج ليزر He – Ne وطرائق تبريده (Latakia University Journal -Basic Sciences Series, 2014)
تحتاج الليزرات لضمان استقرار عملها مع الزمن وثبات مواصفات حزمتها وكفاءتها إلى تبريد المادة الفعالة والعناصر الضوئية الحساسة الملحقة, ويتم اختيار طريقة التبريد المناسبة من الناحية الاقتصادية ومن ناحية سهولة العمل . تساعد تقنية التبريد في إطالة حياة المنابع الضوئية والجمل الليزرية وفي رفع مستوى استقرارها وحُسن تشغيلها, لذلك فإن جملة التبريد الكفوءة لليزرات العلمية والصناعية أساسية عند تصميم الليزر، وهي تساعد في تحسين مواصفات الحزمة الصادرة عن الليزرات الغازية أو الصلبة أو نصف الناقلة ، إضافةً إلى أثرها الجيد في عمر الليزر وأمان استخدامه. تصمم منظومة التبريد التي تحتاجها جملة ليزرية بناءً على كمية الحرارة المتولدة من الجملة( بواحدة J ) , التي يجب على منظومة التبريد إزاحتها لإبقاء الليزر عند درجة حرارة معينة. we seek to ensure laser stability , during its work , with time , and consistency of specifications and efficiency (returns), the cooling of the active medium and optical elements, are sensitive to the proper cooling method, in economic terms and in terms ease of work. Cooling technique helps prolonging the life of laser systems ,its stability and optimizing its operation. So the total cooling efficient lasers , Scientific and Industrial is essential when designing a laser and helps improving the specifications of lasers , gaseous or solid or semiconductor . In addition to that cooling has a good impact on the age of the laser , and safety of its use . The designed cooling system , necessary for a certain laser system , depends on the amount of heat generated from the system(in Joule), which must be removed by the cooling system to keep the laser at specific temperature